2020
DOI: 10.2217/imt-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Activity of Rituximab in the Treatment of Pemphigus

Abstract: B-cells are major effector cells in autoimmunity since they differentiate into plasmocytes that produce pathogenic auto-antibody such as anti-desmoglein antibodies in pemphigus patients. Major advances were obtained using whole B-cell depleting therapies including anti-CD20 antibodies in refractory pemphigus patients that lead to rituximab approval in pemphigus patients in EU and USA. This review summarizes the data supporting the efficacy of rituximab in pemphigus and provides an overview of the reported immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Notably, a high percentage of patients receiving RTX had lymphopenia without disturbance in other hematopoietic cell lineages, which mainly occurred after the first cycle of RTX in patients previously having received cyclophosphamide. Lymphopenia and secondary malignancies are well-known complications of cyclophosphamide use ( 9 , 41 ), whereas they are uncommon adverse events associated with RTX use in AIBD ( 42 ). Previous therapies received by aged population of patients with MMP as well as long term follow-up might have thus contributed to the reported adverse event rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a high percentage of patients receiving RTX had lymphopenia without disturbance in other hematopoietic cell lineages, which mainly occurred after the first cycle of RTX in patients previously having received cyclophosphamide. Lymphopenia and secondary malignancies are well-known complications of cyclophosphamide use ( 9 , 41 ), whereas they are uncommon adverse events associated with RTX use in AIBD ( 42 ). Previous therapies received by aged population of patients with MMP as well as long term follow-up might have thus contributed to the reported adverse event rates.…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with this study ( 43 ), a higher incidence of cancer was not found in patients having anti-laminin 332 antibodies in our studies, whereas it was suggested in other cohorts of patients with MMP ( 30 , 31 , 44 ). Non-infectious and infectious adverse events reported in our cohort included those commonly reported with RTX, notably in other AIBDs such as pemphigus ( 42 ). The percentage of patients with infectious pneumonia adverse events was higher than in other cohorts ( 11 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Numerous clinical studies have demonstrated its beneficial effects on immune tolerance induction through B-cell depletion. [45][46][47][48][49][50] In the present study, we tested the ability of a combination IS treatment with bortezomib and a mouse-specific CD20 mAb (MB20-11) to suppress anti-AAV capsid NAbs and to enable re-dosing of an AAV vector of the same serotype in naïve mice and in mice with pre-existing anti-AAV capsid NAbs using a mouse model of Pompe disease (GAA-KO mice). This strategy, if successful in mice, should be considered in the design of human AAV gene therapy clinical trials where it is well known that readministration will be required.…”
Section: Introductionmentioning
confidence: 99%
“…Rituximab is approved for the treatment of B‐cell lymphoma and autoimmune diseases, including rheumatoid arthritis and anti‐neutrophil cytoplasmic antibody–associated vasculitis, although the indications vary between regions. Since 2001, several case reports and case series have reported remarkable therapeutic effects of rituximab in pemphigus patients 12–15 . Rituximab has already been administered to >500 patients and is recommended as the standard treatment for refractory cases of pemphigus by the European guidelines 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2001, several case reports and case series have reported remarkable therapeutic effects of rituximab in pemphigus patients. 12 , 13 , 14 , 15 Rituximab has already been administered to >500 patients and is recommended as the standard treatment for refractory cases of pemphigus by the European guidelines. 16 , 17 A prospective, multicenter, parallel‐group, open‐label randomized trial showed significant therapeutic effect of rituximab for pemphigus compared with placebo, which prompted the approval of rituximab for pemphigus treatment by health insurance in the United States and Europe in 2018 and 2019, respectively.…”
Section: Introductionmentioning
confidence: 99%